Practice guidelines for teledermatology in Australia. (3rd May 2020) - Abbott, Lisa M; Miller, Robert; Janda, Monika; Bennett, Haley; Taylor, Monica; Arnold, Chris; Shumack, Stephen; Soyer, H Peter; Caffery, Liam J
Abstract: Despite the potential of teledermatology to increase access to dermatology services and improve patient care, it is not widely practised in Australia. In an effort to increase uptake of teledermatology by Australian dermatologists and support best practice, guidelines for teledermatology for the Australian context have been developed by The University of Queensland's Centre for Online Health in collaboration with The Australasian College of Dermatologists' E‐Health Committee. The guidelines are presented in two sections: 1. Guidelines and 2. Notes to support their application in practice, when feasible and appropriate. Content was last updated March 2020 and includes modalities of teledermatology; patient selection and consent; imaging; quality and safety; privacy and security; communication; and documentation and retention of clinical images. The guidelines educate dermatologists about the benefits and limitations of telehealth while articulating how to enhance patient care and reduce risk when practicing teledermatology.